2020
DOI: 10.1093/ageing/afaa071
|View full text |Cite
|
Sign up to set email alerts
|

Impact of frailty on health-related quality of life 1 year after transcatheter aortic valve implantation

Abstract: Background Transcatheter aortic valve implantation (TAVI) brings symptom relief and improvement in health-related quality of life (HRQoL) in the majority of patients treated for symptomatic, severe aortic stenosis. However, there is a substantial group of patients that do not benefit from TAVI. The aim of this study is to investigate the impact of frailty on HRQoL 1 year after TAVI. Methods The TAVI Care & Cure Program is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…4 5 Furthermore, a recent study reported that frailty was associated with a deterioration in the quality of life 1 year after TAVR. 22 Given that CFS represents the patient's functional status similar to the 6MWT, KCCQ-OS or frailty score, we believe our finding that CFS was associated with a poor SI is consistent with prior studies. In this study, Valvular heart disease preprocedural moderate to severe MR was associated with a poor SI.…”
Section: Discussionsupporting
confidence: 90%
“…4 5 Furthermore, a recent study reported that frailty was associated with a deterioration in the quality of life 1 year after TAVR. 22 Given that CFS represents the patient's functional status similar to the 6MWT, KCCQ-OS or frailty score, we believe our finding that CFS was associated with a poor SI is consistent with prior studies. In this study, Valvular heart disease preprocedural moderate to severe MR was associated with a poor SI.…”
Section: Discussionsupporting
confidence: 90%
“…Kobe et al 42 assessed quality of life before and 30 days after TAVI using the Short Form-36 questionnaire; they found that at 30-day follow-up, the mean scores of all but role physical and social functioning were significantly lower for frail patients. Goudzwaard et al 63 assessed quality of life using the Euro-QoL-5-dimension (EQ-5D) scale; they found that at 12 months follow-up, the mean EQ-5D decreased while the mean EQ-Visual Analogue Scale increased.…”
Section: Resultsmentioning
confidence: 99%
“…With the inclusion of geriatricians in the heart team, more specific attention is paid to patient perspectives and preferences, coupled with life expectancy and the influence of the frailty status (i.e. utility vs futility) [10,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%